2020
DOI: 10.1016/j.sleepx.2020.100024
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of sleep patterns in patients with chronic disorders of consciousness

Abstract: Analysis of sleep patterns in patients with chronic disorders of consciousness attracts attention from the perspective of the diagnosis and prognosis of the disease as well as the treatment. Yet, the very existence of normal sleep in patients in a vegetative or minimally conscious state is still a matter of debate. This paper presents a retrospective analysis of overnight polysomnographic records of 40 patients with chronic disorders of consciousness aimed at the possibility of establishing the connection betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Nekrasova and colleagues showed that automated software can detect sleep-related elements (e.g., sleep spindles, slow waves) to perform an R&K-like scoring in DoC patients. 54 This method showed that some organization of sleep stages was only present in 12.5% of 40 patients, none reached NREM2 or REM sleep and only 77.5% showed signs of wakefulness.…”
Section: Standard Sleep Scoringmentioning
confidence: 95%
See 1 more Smart Citation
“…Nekrasova and colleagues showed that automated software can detect sleep-related elements (e.g., sleep spindles, slow waves) to perform an R&K-like scoring in DoC patients. 54 This method showed that some organization of sleep stages was only present in 12.5% of 40 patients, none reached NREM2 or REM sleep and only 77.5% showed signs of wakefulness.…”
Section: Standard Sleep Scoringmentioning
confidence: 95%
“…Prognosis did not increase with increased spindle activity and VS/UWS patients showed more NREM, increased fragmentation and slower activity in both NREM and REM compared to controls. Nekrasova and colleagues showed that automated software can detect sleep-related elements (e.g., sleep spindles, slow waves) to perform an R&K-like scoring in DoC patients 54 . This method showed that some organization of sleep stages was only present in 12.5% of 40 patients, none reached NREM2 or REM sleep and only 77.5% showed signs of wakefulness.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The mere fact of alternating periods of sleep and wakefulness in VS patients is not evidence of the presence of circadian rhythm and remains a debatable issue, including in relation to MCS patients. Severe brain damage that caused the development of DOC (strokes, TBI, anoxic lesions) cannot but disrupt the activity of central oscillators, directly damaging them or destroying links with the periphery, and the level of preservation of circadian rhythms and the dynamics of their recovery can be an informative diagnostic criterion for assessing the patient’s condition [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%